2023
DOI: 10.1128/aac.01312-22
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Empirical Dosing Regimens for Meropenem in Intensive Care Unit Patients Using Population Pharmacokinetic Modeling and Target Attainment Analysis

Abstract: In the present study, population pharmacokinetic (PK) analysis was performed based on meropenem data from a prospective study conducted in 114 critically ill patients with a wide range of renal functions and various disease conditions. The final model was a one-compartment model with linear elimination, with creatinine clearance and continuous renal replacement therapy affecting clearance, and total bodyweight impacting the volume of distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…However, the risk of toxicity-such as neurotoxicity-also increases as the concentration of meropenem increases [35]. A recent study considering both target attainment and potential toxicity reported that the optimal dose regimens were either to administer 2 g every 8 h with 3 h prolonged infusions, or 4 g per day by continuous infusion [36]. Considering these results, administering 1 g of meropenem by 3 h infusion may have provided an insufficient concentration in the ELF against these pathogens-especially those with an MIC > 4 mg/L [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk of toxicity-such as neurotoxicity-also increases as the concentration of meropenem increases [35]. A recent study considering both target attainment and potential toxicity reported that the optimal dose regimens were either to administer 2 g every 8 h with 3 h prolonged infusions, or 4 g per day by continuous infusion [36]. Considering these results, administering 1 g of meropenem by 3 h infusion may have provided an insufficient concentration in the ELF against these pathogens-especially those with an MIC > 4 mg/L [21].…”
Section: Discussionmentioning
confidence: 99%